POTENSI USAHA PARIWISATA ALAM DI KAWASAN WANAWISATA WADUK PONDOK KABUPATEN NGAWI - Puspitawati, Indah Rekyani; Susanto, Anang (JURNAL AGRI-TEK, 2015)
Ngawi manage wealth of the region with the development of Tourism nature, combining forest areas and reservoirs as a alternative to reduce poverty and reduce the number of pre prosperous. A mix of functions between the main function as a provider of irrigation water and function as a tourist destination . The potential of nature tourism businesses are made public and assisted with the PU department (irrigation) is a form of cooperation to increase the role and participation of the community. Currently the potential of doing business in the business community in Ecotourism Development in the reservoir area cottage heavily dependent on the involvement of stakeholders. Based on the required formation Ecotourism Management Board Reservoir cottage to accommodate the interests of stakeholders. Recommendations from this study were (a) the development of attractions Ecotourism in the reservoir hut, (b) the improvement of infrastructure and services that support the attraction Ecotourism, (c) an increase in the promotion and expansion of market opportunities, (d) an increase in the local economy and the strengthening of resources human and (e) of local government policy support in the development of Ecotourism Keywords: alternative, function, potential, business, society